2020
DOI: 10.1016/j.applthermaleng.2020.115863
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of heat transfer enhancement of a heat exchanger tube equipped with double-cut twisted tapes

Abstract: Experimental investigation of heat transfer enhancement of a heat exchanger tube equipped with double-cut twisted tapes. Applied Thermal Engineering, 180. p. 115863.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Fluid flows are classified into three types: laminar, turbulent, and transitional, as shown in Figure 6. The Reynolds number has no dimensions and may be computed using the proper formula [34]. The dye was injected into the dye reservoir at the flow during this experiment in order to visualize the flow over time.…”
Section: Application Of Smart Mathematical Modelling Of Water Consumption With Periodic Time Osborne Reynolds Pipe Flowmentioning
confidence: 99%
“…Fluid flows are classified into three types: laminar, turbulent, and transitional, as shown in Figure 6. The Reynolds number has no dimensions and may be computed using the proper formula [34]. The dye was injected into the dye reservoir at the flow during this experiment in order to visualize the flow over time.…”
Section: Application Of Smart Mathematical Modelling Of Water Consumption With Periodic Time Osborne Reynolds Pipe Flowmentioning
confidence: 99%
“…From the ancient, many experiments and numerical approaches [22][23][24][25][26] were applied to insert the circular tubes as the tabulator creator or vortex generator to enhance the heat transfer in the rectangular channel in such a way a valuable heat exchanger can be made. Also, much literature [27][28][29] can be found that developed the correlations among the fluid dynamics parameter and the non-dimensional parameter which might help design the heat exchanger of any shape. Many of the researchers who had focused on the shape of the heat exchanger for example [30][31][32] have suggested that increasing the heat transfer in the tube dimpled channel proved to be the most beneficial in terms of transferring the heat than the plain tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Not only does perforation enhance the turbulator efficiency, but turbulator-cutting or groove also enhances the effectiveness of the turbulator. In a recent experimental study, the effect of double-cut twisted tape on heat transfer improvements was considered by Nakhchi et al [20]. They found that by increasing the cut ratio from 0.25 to 0.90, the Nusselt number was enhanced up to 177.4%.…”
Section: Introductionmentioning
confidence: 99%